2008
DOI: 10.1021/bp030008n
|View full text |Cite
|
Sign up to set email alerts
|

Biological Reduction of Nitric Oxide in Aqueous Fe(II)EDTA Solutions

Abstract: The reduction of nitric oxide (NO) in aqueous solutions of Fe(II)EDTA is one of the core processes in BioDeNOx, an integrated physicochemical and biological technique for NO(x)() removal from industrial flue gases. NO reduction in aqueous solutions of Fe(II)EDTA (20-25 mM, pH 7.2 +/- 0.2) was investigated in batch experiments at 55 degrees C. Reduction of NO to N(2) was found to be biologically catalyzed with nitrous oxide (N(2)O) as an intermediate. Various sludges from full-scale denitrifying and anaerobic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…On the other hand, microorganism‐mediated bioelectrochemical reaction could also lead to Fe(III)EDTA reduction and this pathway might be predominant in this system for Fe(III)EDTA reduction, evidenced by the detection of abundant potential iron‐reducing bacteria (Fig. S2) and relatively low oxidability of Fe(III)EDTA at neutral pH . The role of hydrogen in the MFC for the reduction of Fe(III)EDTA or even Fe(II)EDTA‐NO can be excluded because there was no hydrogen produced in this system .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, microorganism‐mediated bioelectrochemical reaction could also lead to Fe(III)EDTA reduction and this pathway might be predominant in this system for Fe(III)EDTA reduction, evidenced by the detection of abundant potential iron‐reducing bacteria (Fig. S2) and relatively low oxidability of Fe(III)EDTA at neutral pH . The role of hydrogen in the MFC for the reduction of Fe(III)EDTA or even Fe(II)EDTA‐NO can be excluded because there was no hydrogen produced in this system .…”
Section: Resultsmentioning
confidence: 99%
“…The reactor cannot be strictly gas‐tight and thus a little oxygen might lead to the oxidation of Fe(II)EDTA‐NO. But the most important reason for the slight decrease of Fe(II)EDTA‐NO is the Fe(II)EDTA‐NO reduction coupled with Fe(II) oxidation via Equations (8) and (9) spontaneously or mediated by the biological action . Another batch test (Test 5) was performed to further confirm electron donor for Fe(II)EDTA‐NO reduction, in which both Fe(II)EDTA‐NO and Fe(II)EDTA were injected into the cathode compartment at open circuit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the final product of NO denitrification was mainly N 2 . In the BioDeNOx process, the reduction of NO to N 2 was found to be biologically catalyzed with nitrous oxide (N 2 O) as an intermediate [43]. They found that the NO (aq) and Fe(II)EDTA concentration had an effect on the accumulation rate of N 2 O [44].…”
Section: Analysis Of Reduction Products Of Fe(ii)edta-nomentioning
confidence: 99%